Oman - Quamar, Md. Muddassir; Hameed, Sameena; Kumaraswamy, P. R. (Persian Gulf 2023: India’s Relations with the Region, 2023)
Oman is one of the most important countries in the Gulf region and has gradually been working to regain its political and strategic space after the power transition that brought Haitham bin Tariq al-Said as the new Sultan. Due to Covid-19 and other financial issues, the country has faced economic challenges and has been reaching out to rich GCC neighbours secure financial help and investment to overcome them. At the strategic level, Oman is one of the major regional countries that advocate accommodation of Iran in the regional politics and prefer political dialogue over confrontation to discuss and resolve difference with it and Arab Gulf states. India and Oman share a multidimensional and robust relationship encompassing trade, commerce, defence, security, political and diplomatic ties. Oman continues to attract greater Indian attentions mainly because of its strategic location and the potentials in strengthening economic and defence partnerships.
Keywords: Relations -- Oman -- Inde